EP1216 What are the real-world outcomes of locally advanced cervical cancer patients who receive neo-adjuvant chemotherapy?. (1st November 2019) - Baillie, K; Crearie, C; Laskey, J; Bennie, M; Harrand, R; Sadozye, A; Kerr, A; Reed, N; Graham, K
Abstract : Introduction/Background: Concurrent chemoradiotherapy (CCRT) is the standard of care for locally advanced cervical cancer. However, a significant number of women develop local and/or systemic relapse. Limited studies suggest that neoadjuvant chemotherapy (NACT) may improve efficacy, with 3 year overall survival (OS) of 67% in a recent Phase II study (McCormack M, et al; 2013). In the West of Scotland Cancer Network (WoSCAN), 3-weekly NACT has been used for over a decade in high-risk women. A previous local study in 2012 demonstrated 55% of NACT patients proceeded to CCRT. This study aimed to identify the proportion of patients proceeding to definitive CCRT following NACT in the real-world setting and evaluate survival. Methodology: Data were collected retrospectively from electronic clinical records of WoSCAN patients who commenced NACT between January 2012 and December 2016. Statistical analysis was performed using R®. OS was estimated using Kaplan-Meier method and Cox's proportional-hazards models used to estimate unadjusted hazard ratios (HR). Results: 126 patients were identified; median age was 45 years (range 22–75). The majority had at least FIGO Stage II disease (91.3%) and squamous pathology (85.7%). Para-aortic nodes were present in 10.4% and 4.8% had Stage IVB disease (encompassed within a radical field). NACT regimens consisted primarily of Cisplatin/Paclitaxel (62.7%) or Carboplatin/Paclitaxel (34.9%); a median of 3 cycles were administered. 85.7% proceeded to CCRT, 11.1% received radiotherapy (RT) only, and 3.2% progressed or defaulted. 3 year OS was 74.2% (95% CI 66.4–82.9). Treatment with RT only, significantly increased the death hazard (Unadjusted HR 2.35 (95% CI 1.15–4.79)). Conclusion: Almost 90% of patients proceeded to CCRT. Survival compares favourably with recent Phase II data illustrating that NACT followed by CCRT is a feasible approach for locally advanced cervical cancer, especially in women with bulky disease. Preliminary data are encouraging, but results of Phase III INTERLACE trial are still awaited. Disclosure: This study was funded by the Scottish Government. The authors declare no competing interests.